The Risk of Cervical Cancer from Smoking in Indonesia - ., Besral; Pratama, Ivan Arif (KnE Life Sciences, 2018)
Cervical cancer is cancer frequently strikes women around the world. One of the factors precipitating these cancers is smoking. The proportion of smokers among Indonesian women has been increased every year for the past ten years. This study aimed to assess Indonesian women’s risk of developing cervical cancer from smoking. A cross-sectional study design was used, using Basic Health Research data for the year 2013 that were collected from 33 provinces in Indonesia. 216,797 female respondents over 20 years old were selected randomly. The prevalence of cervical cancer in this sample is 120 per 100,000 women over 20 years old (95% CI = 100–140 per 100,000). Multivariate logistic regression shows that women who smoke daily have a 2.3 times greater risk of suffering from cervical cancer than women who have never smoke. Women who are ex-smokers but who previously smoked every day have a 9.6 times greater risk of suffering from cervical cancer than women who have never smoke. Other risk factors are being 50 or older (OR 3.0), having a history of abortion (OR 1.6), having had sex before the age of 18 (OR 1.6). Having a low or mid-level economic status decrease the risk of cervical cancer (OR 0.4 or 0.6). Using birth control pills also decrease the risk of cervical cancer (OR 0.2). Smokers and ex-smokers have similar high risks of developing cervical cancer. It is recommended that women avoid tobacco or cigarette consumption from an early age. The dangers of various diseases, including cervical cancer, is potentially life threatening. Strong government policies are needed to avoid the dangers of teen smoking. Keywords: Cervical cancer, smokers, ex-smokers, GOTGOT Indonesia